(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The aim of this paper is to suggest a structure for automatic complex for putting art images on separate details from wood material. For the putting of images is used tampon automatic stamp. The project parameters of the automatic complex are defined. 2D drafts and 3D models of the suggested variants are worked. An analysis and evaluation of the worked variant is made and the optimal was chosen which was projected and researched. The automatic complex was realized and experimental studies were done and part of the results were made in the present study.